2019
DOI: 10.3390/polym11122107
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Bamboo Fibers to Enhance the Interfacial Adhesion of Epoxy Resin-Based Composites Prepared by Resin Transfer Molding

Abstract: Bamboo fibers (BFs)-reinforced epoxy resin (EP) composites are prepared by resin transfer molding (RTM). The influence of BFs surface modification (NaOH solution or coupling agents, i.e., KH550 and KH560) on interfacial properties of BFs/EP composites is systematically investigated. The synergistic effect of hydrolysis, peeling reaction of BFs, and the condensation reaction of hydrolyzed coupling agents are confirmed by FTIR. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) reveal that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It was reported that various modification methods aiming at overcoming the incompatibility and refining the interfacial adhesion between polymer and fiber, include chemical modification of bamboo-powder surface or the addition of appropriate compatibilizer, and the latter was the most effective way to overcome two-phase incompatibility [12,[16][17][18][19]. The most used in situ reactive compatibilizers to compatibilize PBAT and natural fibers contain epoxy or diisocyanate groups, which could easily form chemical bonds between both PBAT and natural fiber [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that various modification methods aiming at overcoming the incompatibility and refining the interfacial adhesion between polymer and fiber, include chemical modification of bamboo-powder surface or the addition of appropriate compatibilizer, and the latter was the most effective way to overcome two-phase incompatibility [12,[16][17][18][19]. The most used in situ reactive compatibilizers to compatibilize PBAT and natural fibers contain epoxy or diisocyanate groups, which could easily form chemical bonds between both PBAT and natural fiber [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical characteristics of the interface are responsible for the mechanical properties of the composite as a whole. However, both interface and interphase help with the mechanical properties of the composite material, the main one being the adhesion of the material [ 104 ].…”
Section: Interface Between Fiber-matrixmentioning
confidence: 99%
“…When electrostatic attraction occurs between the matrix and the reinforcement, electrical charges are transferred from one to the other, leading to the formation of a negative charge on one substrate and a positive charge on the other. This generates an electrostatic attraction between the composite components [ 104 ]. Chemical adhesion is given by bonds of the electronic structure during the formation of the interface.…”
Section: Interface Between Fiber-matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve weak interfacial adhesion of existing CFRCs, various approaches for surface modification of CFs were extensively investigated ( Prakash and Rajadurai, 2017 ; He et al., 2021 ; Dai et al., 2011 ; Andideh and Esfandeh, 2016 ; Wang et al., 2019 ; Chukov et al., 2019 ; Sun et al., 2020 ; Sepe et al., 2018 ; Nie et al., 2017 ; Hu et al., 2018 ; Huan et al., 2020 ; Zhu et al., 2017 ; Zhang et al., 2020b ; Fu et al., 2019 ). The main purpose of these strategies is to improve the interfacial bonding strength between fibers and the matrix by providing more physical contact for mechanical interlocking, thereby creating rich active groups or good wettability for chemical bonding ( Karnati et al., 2020 ; Raphael et al., 2018 ; Sharma et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%